Cavitation Detection and Prevention in Professional Warewashing Machines. (November 2016) - Burlon, F.; Micheli, D.; Furlanetto, R.; Simonato, M.; Cucit, V.
Abstract: Cavitation is a phenomenon characterised by the presence of vapour bubbles in the fluid led by a local drop in pressure. In literature it is well known the impact on cavitation of pressure and temperature of pure water, but there are only few studies analysing how the presence of certain components of detergents and additives can influence the phenomenon. The impact of detergents and additives could be explained by the modified viscosity and rheology of the solution but also by the variation in the vapour tension. Most of these effects are due to the presence of surfactants and polymers in the solution. Cavitation in dynamic pumps is an important aspect that needs to be monitored and prevented, because it can cause damages affecting pump performances and inducing an increment in the level of vibration and noise. In professional warewashing machines, as for example the models of Electrolux Rack Type, this phenomenon can affect the operating functionalities of the machine. An experimental pump test rig has been realized with the aim of studying and monitoring the influence of these parameters on cavitation inception. This test rig permits measuring the pump performances at various operating conditions, in order to obtain its characteristic curves, and also forcing cavitation to measure its Net Positive Suction Head required (NPSHr) at different flow rates. The pump test rig allows also testing various configurations of the pump at different cavitation conditions, obtained by changing not only the suction pressure and temperature of the fluid but also its properties, adding detergents and additives. Cavitation inception can be detected measuring both the corresponding prevalence decrease and the change of vibration and noise level.